Plasma Myostatin is only a Weak Predictor for Weight Maintenance in Obese Adults - Tsioga, M. N.; Oikonomou, D.; Vittas, S.; Kalscheuer, H.; Roeder, E.; Wintgens, K. F.; Nawroth, P. P.; Wolfrum, C.; Rudofsky, G. (Experimental and Clinical Endocrinology & Diabetes, 2015)
Background: Predicting an individual’s success in a non-surgical weight loss approach is a demanding need since obesity is becoming an epidemic burden. A possible predictive marker is myostatin, a member of the transforming growth factor b superfamily, which has been shown to be an important regulator of muscle homeostasis.Methods: In the present study, we analyzed myostatin as a marker to predict weight loss of patients that participated in a 2 phased weight reduction program, comprising a weight loss period of 12 weeks and a weight stabilization period of 40 weeks. Therefore, 62 obese individuals with a mean BMI of 40.6 kg/m2 were included. Plasma myostatin was measured with ELISA at the beginning (T0), after weight loss (T1) and at the end of the program (T2).Results: Although significant weight loss of −23.9±14.9 kg was achieved, myostatin did not change significantly during the program (T0>T1: p=0.46; T1>T2: p=0.70; T0>T2: p=0.57). Myostatin at baseline did neither negatively correlate with the achieved weight loss in the weight reduction phase (T0>T1: r=0.27, p=0.16) nor with weight loss during the whole program (T0>T2: r=0.20, p=0.29). Only a minor correlation with myostatin levels after weight loss with weight regain during maintenance period was detected. (T1>T2: r=−0.37, p=0.05).Conclusion: Plasma myostatin might be suitable in predicting weight regain after marked weight loss, but no association with weight loss was observed in patients undergoing a non-surgical weight loss program. Therefore, myostatin does not seem to be a predictor for success in non-surgical weight loss approaches.
Keywords: myostatin; obesity; weight reduction; weight stabilization